MIMO relaying UAVs operating in public safety scenarios - Viana, Joseanne (2022)
Funding: This research received funding from the European Union’s Horizon 2020 research and innovation program under the Marie Sklodowska-Curie Project Number 813391 Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.